Conjunctival melanoma in children: a systematic review - Partyka, Maria; Plewniok, Julia; Janeczek, Maksymilian; Kantor, Karolina Kinga; Szymańska, Wiktoria Maria; Wójcik, Julia; Pamuła, Kacper Wojciech; Cholewa, Marcin; Kuca, Maciej; Jaglarz, Karolina (Journal of Education, Health and Sport, 2024)
Introduction and Objective: Conjunctival melanoma (CM) is rare, particularly in children. It’s characterized by high aggressiveness and a tendency to metastasize. Due to the limited number of published case reports and studies in the pediatric population, it’s difficult to standardize diagnostic and therapeutic procedures. The aim of this paper is to collect and systematize the available information on cases of conjunctival melanoma in children. Materials and Methods: Two databases were used for the review: PubMed and Scopus. Additionally, references were manually searched. After removing duplicates, 283 articles were obtained, of which 20 were included in the review. The analysis included articles in English that contained detailed information on the course of CM in children. Abbreviated Description of the State of Knowledge: Conjunctival melanoma accounts for 2-5% of all eye tumors. Clinically, it presents as a pigmented lesion with heterogeneous shape and structure. Its development may be associated with UV radiation and genetic mutations. In diagnostic process, an ophthalmological examination is crucial, along with the search for potential metastases and recurrences. Treatment primarily involves surgical removal, with the addition of cryotherapy, chemotherapy, and radiotherapy if necessary. Summary: Despite rare occurrence of CM, due to its high aggressiveness, every conjunctival lesion should be thoroughly examined with oncological vigilance. The amount of data on this subject is limited, so further research is needed to help develop prognosis and management strategies. A greater number of studies in the future may also contribute to the development of new therapeutic options, thereby improving outcomes.